The role of women during the Spanish Civil War: A Historiographical Mapping Through Bibliometrics and Network Analysis - Orduña Prada, Mónica; Moreno-Delgado, Alicia (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
This study explores the multifaceted roles of women during the Spanish Civil War, examining the diverse perspectives delineated in academic literature. Leveraging scholarly articles sourced from Web of Science and Scopus spanning from 2013 to 2022, we analyse temporal trends, author demographics, scholarly impact, journal prominence, and thematic content. Our investigation culminates in the classification of contributions into six overarching themes: humanitarian aid and healthcare, biographical narratives, communication dynamics, experiences of exile and refugee communities, women’s mobilisation and ideological engagement, and the harrowing realities of repression and violence inflicted upon women. Furthermore, our findings reveal that research predominantly originates from Spain and is disseminated through Spanish-language journals. However, there exists a notable interconnection with the United States, evidenced by the participation of prominent North American authors and publication in non-Spanish journals. This research offers insights into the multifaceted roles of women during the Spanish Civil War and their academic representation.